Sistem Pendidikan Anak Usia Dalam Konsep Islam (Analisis dalam Teoritis dan Praktis) - Suradi, Ahmad (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2018)
This article aims to reveal how the education system developed for early childhood in the Islamic concept, which includes curriculum, methods and evaluation of education. The method used in this paper is descriptive qualitative method. The results of the discussion indicate that the education that should be given to early childhood, is to include; first, the aqidah education, this is given because Islam puts the education of faith in the most fundamental position, Second, the Education of worship, so that someday they grow into beings who really piety, that is the devout man to carry out all religious commands and obedient also in steer clear of any ban. Third, moral education, in order to educate morals to the children, in addition to be given the right example, should also be shown about how to respect and to manners with fellow human beings. Islamic educational methods that can and should be applied to early childhood educational activities are exemplary methods, methods of practice and practice, game methods, songs, and stories, methods of targhib and tarhib, methods of praise and flattery and inculcation of good habits. The evaluation for the assessment of the educational process of children at an early age can be done in various ways, among others through the observation and recording of anecdotes which is a record of the attitude and behavior of children.